Principles & Aims of Guidance in Education: Facilitating balanced development through guidance (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Guidance in simple terms means to direct or provide assistance to someone who needs help. In the broader perspective, guidance is provided at all levels to human beings by one person or the other. For instance, in a family, the head of the family may guide other family members to act in a certain manner. In other words, guidance can help a person solve a personal, vocational, educational or any other problem for which he is unable find a solution on his own. Thus, guidance has emerged as both a process and a concept. Guidance is, therefore, interpreted in different ways, especially, when it comes to education. As a concept, guidance deals with maximum development of an individual to ensure that the individual can take his own decisions. As a process, guidance involves making an individual aware of his capabilities and skills. Guidance as a process helps an individual to make the right decisions in various aspects of life so that a balanced development of the individual can be facilitated.